Possibility of discrete beam propagation in chiral nematic liquid crystals - Kwaśny, Michał; Laudyn, Urszula A.; Jung, Paweł; Karpierz, Mirosław A. (Photonics Letters of Poland, 2009)
This work presents an experimental and theoretical analysis of beam propagation in multiple layers formed by chiral nematic liquid crystal. Depending on structure parameters light can be guided in a single layer or propagate in a matrix of coupled layers in a discrete way. It is also shown that the nonlinear behavior leads to creation of spatial solitons (nematicons) in both discrete and single-layer configurations. Full Text: PDF References: I. C. Khoo, S. T. Wu, Optics and Nonlinear Optics of Liquid Crystals, World Scientific Publ., Singapore (1997) G. Assanto, M. Peccianti, C. Conti, "Nematicons: Optical Spatial Solitons in Nematic Liquid Crystals", Opt. Photon. News 14, 44 (2003)[CrossRef] M. A. Karpierz, Soliton Driven Photonics, Boardman, A. D. Sukhorukov, A.P., (Eds.), p.41, Kluwer Academic Publishers: Dordrecht U. A. Laudyn, K. Jaworowicz, M. A. Karpierz, "Spatial Solitons in Chiral Nematics", Mol. Cryst. Liq. Cryst. 489, 1563 (2008)[CrossRef] U. A. Laudyn, M. Kwasny, M. A. Karpierz, "Nematicons in chiral nematic liquid crystals", Appl. Phys. Lett., 94, 091110 (2009)[CrossRef]